Penatalaksanaan Holistik Gagal Jantung Kongestif Dan Hipertensi Pada Wanita Usia 65 Tahun Melalui Pendekatan Kedokteran Keluarga - Isabel Theodora; Sahab H Sibuea (CV. Jasa Sukses Abadi, 2023)
Heart disease is the highest cause of death worldwide for the last 20 years. The prevalence of CHF in Indonesia according to Riskesdas in 2018 was 1.5%, while the prevalence in Lampung in 2013 was estimated at around 5560 patients. Hypertension is a global health problem with the biggest morbidity rate in the world. In Indonesia, the estimated number of cases of hypertension is 63,309,650 people, while in Lampung, is around 6,216,638 cases. This research aims to implementing a holistic and comprehensive approach of a family doctor according to the problems experienced by patients and patient management based on evidence based medicine, patient centered, family oriented and community oriented. Primary data was obtained through autoanamnesis, physical examination and home visits. Secondary data was obtained from patient's medical record. Assessment based on a holistic diagnosis from the beginning of the process and the final study qualitatively and quantitatively. In results patient Mrs. H, 65 years old, came to the Health Center to ask for a routine drug referral, the patient had complaints of congested breath when doing strenuous activities and improved while resting. The patient was diagnosed with CHF 10 years ago and hypertension 20 years ago. Patient has a high salt and fat diet, low physical activity, lack of knowledge and family support regarding the patient's disease and treatment. Furthermore, the management of patients is carried out according to the theory and related journals. At the time of evaluation, patients can follow the recommendations for both pharmacological and non-pharmacological therapy. Holistic management can increase knowledge and change the patient’s behavior. The role and support of the family are needed in the treatment of the patient in order to drugs consumption monitoring.